Successful management of acute promyelocytic leukemia in the third trimester of pregnancy: a case report and review of the literature - Puttirangsan, Sirichai; Prasertkanchana, B.; Parapob, Natnipa; Srichairatanakool, Sirichai; Rattanathammethee, Thanawat (Frontiers in Hematology, 2025)
Acute promyelocytic leukemia (APL) during pregnancy is an exceptionally rare occurrence with high maternal and fetal mortality rates, requiring a highly tailored approach to therapy. We report a case of a patient diagnosed with APL during the third trimester of pregnancy who initially presented with spontaneous ecchymoses. Treatment was initiated with all-trans retinoic acid (ATRA) and a modified dose of idarubicin, leading to a rapid correction of the coagulopathy and a complete remission of the APL. The patient subsequently underwent induced labor, resulting in an uncomplicated vaginal delivery without significant hemorrhage and no evidence of embryopathy in the neonate. To date, no published reports of successful deliveries in patients with APL have been documented in Thailand. This case highlights how a multidisciplinary approach involving obstetricians, hematologists, and neonatologists ensured both maternal survival and optimal neonatal outcomes.